2013
DOI: 10.1161/circresaha.113.301792
|View full text |Cite
|
Sign up to set email alerts
|

A Role for the Endothelium in Vascular Calcification

Abstract: Rationale Vascular calcification is a regulated process that involves osteoprogenitor cells and frequently complicates common vascular disease such as atherosclerosis and diabetic vasculopathy. However, it is not clear if the vascular endothelium has a role in contributing osteoprogenitor cells to the calcific lesions. Objective To determine if the vascular endothelium contributes osteoprogenitor cells to vascular calcification. Methods and Results In this study, we use two mouse models of vascular calcifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
227
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 183 publications
(242 citation statements)
references
References 43 publications
13
227
0
2
Order By: Relevance
“…Tissue sections were fixed, processed, and stained as previously described (35). Immunofluorescence was performed as previously described in detail (36,37). Cultured cells were grown in chamber slides and fixed in 4% (wt/vol) paraformaldehyde for 30 min, permeabilized with 0.1% Triton X-100, blocked with 1% goat serum and 1% BSA in TBS, and stained using the same protocol as for the tissues.…”
Section: Methodsmentioning
confidence: 99%
“…Tissue sections were fixed, processed, and stained as previously described (35). Immunofluorescence was performed as previously described in detail (36,37). Cultured cells were grown in chamber slides and fixed in 4% (wt/vol) paraformaldehyde for 30 min, permeabilized with 0.1% Triton X-100, blocked with 1% goat serum and 1% BSA in TBS, and stained using the same protocol as for the tissues.…”
Section: Methodsmentioning
confidence: 99%
“…This model is supported by immunohistochemical analysis of the expression of Sox2, Oct4 and Nanog within the TZ and in vitro data demonstrating upregulation of these genes in cartilage explants cultured with HUVEC conditioned medium (Figs 4,7,11). However, Yao et al have shown that Sox2, Oct4 and Nanog can be induced in endothelial cells by elevated Bmp signaling, so it is possible that endothelial cells are also being induced to express the pluripotency programs (Yao et al, 2013); but lineage-tracing experiments demonstrate that the vast majority of the expression is in chondrocyte-derived cells (Fig. 7R-…”
Section: Role Of the Vasculature In The Transformation Of Chondrocytementioning
confidence: 99%
“…However, postnatally, phenotypic transitions are linked to pathological processes, such as tumor metastasis and the occurrence of fibroproliferative diseases. EndMT has been shown to contribute to the formation of neointimal lesions (Cooley et al, 2014;Moonen et al, 2015), vascular calcifications (Yao et al, 2013), and fibrosis of the lungs (Hashimoto et al, 2010), heart (Zeisberg et al, 2007) and kidneys , as well as heterotypic ossifications (Medici and Olsen, 2012).…”
Section: Introductionmentioning
confidence: 99%